STEAM PADA MODEL PjBL DAN HASIL BELAJAR KOLOID PESERTA DIDIK - Sugiarti; Taty Sulastri; Syarifah Fatimah (Universitas Negeri Makassar, 2023)
Chemistry learning at SMA Negeri 7 Takalar is still dominated by ordinary cooperative learning. Students still have difficulty understanding colloid lessons where the material is conceptual and requires the application of concepts contextually. Therefore it is very important to do learning that involves students actively applying colloid theory and concepts through the STEAM approach to the Project Based Learning (PjBL) learning model. This research is a quasi-experimental research which aims to determine the learning outcomes of Colloid Students after learning with the STEAM approach in the PjBL Model Class XI MIPA SMA Negeri 7 Takalar. The research design was posttest only control group design. The population is all students of class XI MIPA SMA Negeri 7 Takalar which consists of three classes. The research samples for Class XI MIPA 2 and Class XI MIPA 3 as the experimental and control groups were randomly selected. The results of the descriptive analysis show that the average learning outcomes of the experimental class are higher than the control class. The results of the inferential statistical test showed that the learning outcomes of students using the t test at a value of α = 0.05 obtained tcount > ttable (2.83 > 1.99). The results of data analysis from hypothesis testing stated that the STEAM approach to the Project Based Learning Model had a significant influence on the colloidal learning outcomes of Class XI MIPA Students at SMA Negeri 7 Takalar